Translation as a Linguistics Process: A Case Study of the Concept of Equivalence in Translation TL----SL - Ariremako I. A; Badmus-Lawal K; M. Nazar (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
In this study, the linguistics processes guiding the concept of equivalence in translation of Source Language and Target Language are vividly discussed. When translating from one language to another, it's necessary to decode the source text and look for an acceptable translation in the target language. The main purpose of this paper is to explain the concept Equivalence in Translation to this end. The data used were drawn from some Yoruba lexical words, idioms, proverbs and figurative expressions as well as its English equivalents. According to the most authoritative research in the fields of grammar and sociolinguistics, grammatical analysis is insufficient to explain the nature of language. The results also show that knowledge of a language is a composite of knowledge of a language's structure and usage in a socio-cultural setting.